An efficient and environmental friendly strategy for alumina extraction and Fe–Si alloys production from coal fly ash by combining vacuum thermal reduction, alkali dissolving, and magnetic separation. (1st July 2023) - Yu, Wenzhou; Rao, Zitao; Yuan, Haitao; Wei, Peng; Nyarko-Appiah, Joseph Emmanuel; Jiang, Weiyan
Abstract: With the strengthened awareness of environmental protection and the growing interests of wastes recycling, extraction of valuable metals from coal fly ash (CFA) has drawn extensive attention all over the world. In this paper, an environmental friendly strategy for alumina extraction and Fe–Si alloy production from CFA by combining vacuum thermal reduction, alkali dissolving, and magnetic separation was proposed. The results indicate that the stable mullite phase (Al6 Si2 O13 ) of CFA could be converted into CaO·xAl2 O3 and Fe–Si alloy successfully during the vacuum thermal reduction with the assistance of CaO and Fe2 O3 . Additionally, the produced CaO·xAl2 O3 can be dissolved subsequently by the alkali solutions to extract alumina and generate CaCO3, while the Fe–Si alloy cannot be dissolved. Finally, the CaCO3 and Fe–Si alloy in the dissolving residues can be separated effectively by magnetic separation. In this process, the alumina extraction rate attained 94.62% and there almost no waste was generated, indicating that an efficient and environmental friendly approach for valuable metals recovery from CFA was obtained. Graphical abstract: Image 1 Highlights: The mullite was converted into CaO·xAl2 O3 and Fe–Si alloys after vacuum reduction. The CaO·xAl2 O3 was dissolved by alkali solutions to extract alumina. A 94.62% of alumina extraction rate was achieved by using the new process. The Fe–Si alloys and CaCO3 were separated effectively by magnetic separation.